On the interaction of scrape off layer filaments. (10th November 2017) - Militello, F; Dudson, B; Easy, L; Kirk, A; Naylor, P
Abstract: The interaction of L-mode and inter-ELM scrape-off layer (SOL) filaments is investigated by simulating the dynamics of two seeded density perturbations with different initial separation. A numerical campaign of 2D and 3D simulations is presented to explore the effect that different filaments' perpendicular size and relative distance have on their reciprocal action. It is shown that the interaction is weak unless the filaments are in close proximity, i.e. with a separation of the order of the filaments' diameter in the drift plane. The interaction occurs when the dipolar electrostatic fields associated with the filaments merge or cancel each other and it leads to changes in the radial velocity in the centre of mass of the system that are modest ( ≤ 50 % ) and quickly decaying with separation. These results show that filaments travelling in the SOL can be considered to a good approximation as independent entities.